Implementation of Heart Management In Human Resources Management - Barham Siregar; Alwi F ahruzi Nasution; Angga Arjunes; Ahmad Karim; Ari Kartiko (At-Tarbiyat, 2021)
Humans are the brightest creatures created by God Almighty above all other creations. Therefore there needs to be a way to make it easier to manage human resources. In managing human resources, good abilities are needed in understanding these human resources. As the formulation of the problem in this study aims to determine how the application of heart management (manajemen kalbu) and the benefits felt by the students and congregations who apply it, which is then analyzed and described the application of heart management and its benefits in their daily lives. To find out the answer to the formulation of the problem, the researcher took the object of research to the students and congregation of the Sahlul Manal Islamic Boarding School. After collecting data through the process of interviewing, observing, and then documenting, the information obtained was analyzed using qualitative descriptive analysis techniques to describe the facts that were found related to this research. From the results of the research conducted, it can be concluded that the implementation of heart management at the Sahlul Manal Islamic Boarding School is to fill the heart with dhikr remembering Allah with the hope that the heart is always in a clean state. The benefits felt by the students and congregation are that they get a peaceful life, are more patient and sincere, and are afraid to commit immorality to God.